Evaluation of Protective Mask Notifications to the Safety Gate/RAPEX System during the COVID-19 Pandemic - Wierzowiecka, Joanna; Dąbrowska, Victoria (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: This study aims to assess the protective mask notifications used in the Safety Gate / RAPEX system (an early warning system for managing safety used by the European Commission) between 2020 and 2022 in the context of the COVID-19 pandemic. This study continues research into the impact of the COVID-19 pandemic on the notification of protective masks for this system.Research Design & Methods: Legacy data analysis combines literature evaluation and critique with document research method.Findings: Notifications on protective masks offered between 2020 and 2022 were analysed taking into account four factors: the types of legal provisions that were not met, the non-compliances uncovered, and the categories of voluntary and required measures applied. In 2020, 41% of notifications failed to refer to a specific standard pertaining to the regulation on personal protective equipment. In contrast, during the two subsequent years, we can observe a systematic decrease in the lack of standard indication. Between 2020 and 2022, the reasons for notifications against protective masks that occurred most frequently included ineffective filtration and the lack of adequate testing of the product by a competent body. Voluntary and required measures taken by economic entities against non-compliant protective masks that may pose risks to consumers have been characterised.Implications / Recommendations: The COVID-19 pandemic affected the completeness of notifications for protective masks in the Safety Gate/RAPEX system and the availability of protective masks that were not tested and had ineffective filtration, to consumers. Voluntary and required measures mostly included product withdrawals from the market and from end users. It is recommended that Member State regulatory authorities improve the quality of the notifications provided.Contribution: Notifications on protective masks are characterised in the Safety Gate/Rapex system in the context of the COVID-19 pandemic. The need for continuous improvement of the effectiveness of European market surveillance and the dangerous products early warning system was identified.